Hospital-acquired conditions and length of stay in the pregnancy and puerperal cycle - Silva,Thales Philipe Rodrigues da (2019)
ABSTRACT OBJECTIVE To analyze the impact of the Hospital-Acquired Conditions (HAC) in women in the puerperal and pregnancy cycle during length of stay. METHODS This cross-sectional study was conducted with 113,456 women, between July 2012 and July 2017, in Brazil’s national hospitals of the supplementary healthcare networks and philanthropists accredited to the Unified Health System (SUS). Data on hospital discharges were collected using the Diagnosis-Related Groups (DRG Brasil®) system. All DRGs of the major diagnostic category 14 (MDC14), including pregnancy, childbirth and puerperium, were included. The impact of HAC on length of stay was estimated by Student’s t-test, and the effect size by Cohen’s d, which allows to assess clinical relevance. RESULTS The most prevalent diagnostic categories related to MDC14 were vaginal and cesarean deliveries without complicating diagnoses, both at institutions accredited to SUS and those for supplementary health care. The prevalence of HAC was 3.8% in supplementary health and 2.5% in SUS. Hospitals providing services to supplementary health care providers had a longer length of stay considering HAC for patients classified as DRG: cesarean section with complications or comorbidities at admission (p < 0.001; Cohen’s d = 0.74), cesarean section without complications or comorbidities at admission (p < 0.001, Cohen’s d = 0.31), postpartum and post abortion without listed procedure (p < 0.001, Cohen’s d = 1.05), and other antepartum diagnoses with medical complications (p < 0.001; Cohen’s d = 0.77). CONCLUSIONS This study showed that the prevalence of HAC was low both in the institutions accredited to attend by SUS and in those of supplementary health; however, its presence contributes to increasing the length of stay in cases of cesarean sections without complications or comorbidities in supplementary health institutions.